A novel STING agonist for cancer immunotherapy and a SARS-CoV-2 vaccine adjuvant. Issue 4 (17th December 2020) - Wu, Jun-Jun; Zhao, Lang; Han, Bei-Bei; Hu, Hong-Guo; Zhang, Bo-Dou; Li, Wen-Hao; Chen, Yong-Xiang; Li, Yan-Mei
Abstract : A novel STING agonist was synthesized and successfully applied to cancer immunotherapy and as a SARS-CoV-2 vaccine adjuvant. Abstract : A novel STING agonist, CDG SF, ipsilaterally modified with phosphorothioate and fluorine, was synthesized. The phosphorothioate in CDG SF might be a site for covalent conjugation. Injection of CDG SF generated an immunogenic ("hot") tumor microenvironment to suppress melanoma, more efficiently than dithio CDG. In particular, immunization with SARS-CoV-2 spike protein using CDG SF as an adjuvant elicited an exceptionally high antibody titer and a robust T cell response, overcoming the drawbacks of aluminum hydroxide. These results highlighted the therapeutic potential of CDG SF for cancer immunotherapy and the adjuvant potential of the STING agonist in the SARS-CoV-2 vaccine for the first time.